Rh/Cr2O3 and CoOx Cocatalysts for Efficient Photocatalytic Water Splitting by Poly (Triazine Imide) Crystals - Liu, Minghui; Zhang, Guigang; Liang, Xiaocong; Pan, Zhiming; Zheng, Dandan; Wang, Sibo; Yu, Zhiyang; Hou, Yidong; Wang, Xinchen (Angewandte Chemie International Edition, 2023)
In situ photo‐deposition of both Pt and CoOx cocatalysts on the facets of poly (triazine imide) (PTI) crystals has been developed for photocatalytic overall water splitting. However, the undesired backward reaction (i.e., water formation) on the noble Pt surface is a spontaneously down‐hill process, which restricts their efficiency to run the overall water splitting reaction. Herein, we demonstrate that the efficiency for photocatalytic overall water splitting could be largely promoted by the decoration of Rh/Cr2O3 and CoOx as H2 and O2 evolution cocatalysts, respectively. Results reveal that the dual cocatalysts greatly extract charges from bulk to surface, while the Rh/Cr2O3 cocatalyst dramatically restrains the backward reaction, achieving an apparent quantum efficiency (AQE) of 20.2 % for the photocatalytic overall water splitting reaction. Poly (triazine imide) modified with Rh/Cr2O3 and CoOx as H2 and O2 evolution cocatalysts, respectively, largely improves the charge separation efficiency and restrains the undesired backward reaction, achieving an apparent quantum efficiency of 20.2 % for photocatalytic overall water splitting.